Agricultural employment in Spain and new Keynesian economics - Andrés González-Moralejo,Silvia (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2016)
Our research examines the agricultural labor market from the perspective of new Keynesian economics. Our aim is to verify that total gross output, total factor productivity, and real wages act as determinants of employment levels in Spanish agriculture. Three structural econometric models were estimated using census data for the period 1998-2013. This was a period of profound economic and social change, and the following two distinct sub-periods were compared: 1998-2007 (a period of economic boom) and 2008-2013 (a period of recession). The empirical evidence is consistent with neo-Keynesian theoretical posits, albeit with certain qualifiers derived from the specifically rural nature of the evidence. The results show a negative relationship between employment and productivity and wages, which intensified during the recession.